Charles S. Peirce and Religion: Biographic Elements and Main Writings - Barrena, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Peirce's relationship with religion, both in his personal life and in his thought, was deeper than has been considered so far. The question of God was for him more important than it might seem at first glance. His writings contain numerous references to religious issues, closely linked to his most important notions of philosophy and science. In this article, the most important biographical data to understand Peirce's relationship with religion are provided; his main notions about God are also examined and, finally, a brief analysis of the most important Peircean writings on religion is made.